Pengaruh Good Corporate Governance Dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan di BEI Periode 2017-2019 - Muhammad Bahril Ilmiddaviq (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
Effectivity of good corporate governance can improve company performance and benefit shareholders. Good corporate governance practices can produce high-quality annual reports that will be provided to inventors, thereby increasing the credibility of the financial statements. The existence of good governance reflects that its financial performance is also good. The purpose of this research is to find out the effect of Good Corporate Governance, and financial performance on company value through secondary data sourced from the annual report data of mining companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Purposive sampling method was chosen and used in this study and got 20 companies as samples. Data analysis using Partial Least Square software. The results of this study indicate that Good Corporate Governance has no effect on firm value. because the company has not all implemented the principles of Good Corporate Governance. Financial performance has an effect on firm value. because the returns taken are large, the stakeholders' welfare will also be guaranteed. It will make the value of the company increase